Feedback from research participants: are member checks useful in qualitative research?. Issue 1 (2nd January 2017) - Thomas, David R.
ABSTRACT: It is often assumed that use of so-called "member checks" improves the credibility of qualitative research. Published literature mentioning member checks was reviewed to identify the purposes and procedures for seeking feedback from research participants as well as outcomes reported from member checks. Four themes reflecting underlying assumptions about the purposes of research that have implications for member checks were identified: theory generalisation, representation, participation, and change. Member checks are unlikely to be relevant to research focussed on theory development and generalisation. For other types of research, member checks might be justifiable, but there was little evidence that member checks improved research findings. Member checks can be useful for obtaining participant approval for using quotations or case studies and where anonymity cannot be guaranteed. In evaluation, stakeholder reviews of draft reports can be seen as good research practice. In participatory or collaborative research, ongoing contact might include member checks.